On the optimal "lockdown" during an epidemic - Martín Gonzalez-Eiras; Dirk Niepelt (University of Bern, Department of Economics, 2020)
We embed a lockdown choice in a simplified epidemiological model and derive formulas for the optimal lockdown intensity and duration. The optimal policy re- ects the rate of time preference, epidemiological factors, the hazard rate of vaccine discovery, learning effects in the health care sector, and the severity of output losses due to a lockdown. In our baseline specification a Covid-19 shock as currently expe- rienced by the US optimally triggers a reduction in economic activity by two thirds, for about 50 days, or approximately 9:5 percent of annual GDP.
Keywords: I18; 330; Epidemic; pandemic; lockdown; social distancing; production shortfall; health care system; Covid-19; SIR model; logistic model